Answer:
x^3-4x^2+25x-100
Step-by-step explanation:
We have 2 roots -5i and 4. Using the conjugate root theorem for the root -5i, we know that 5i should be another root
Combining the roots into a polynomial gives us:
(x+5i)(x-5i)(x-4)
Expand:
(x^2 + 25)(x-4)
x^3-4x^2+25x-100
Split the second term in 6x^2 + 17x + 5 into two terms
6x^2 + 15x + 2x + 5 = 0
Factor out common terms in the first two terms, then in the last two terms.
3x(2x + 5) + (2x + 5) = 0
Factor out the common term 2x + 5
(2x + 5)(3x + 1) = 0
Solve for x
<u>x = -5/2, -1/3</u>
C. 42.39 times 0.1 is 4.239. 42.39-4.239= 38.151 which rounds to 38.15